THE IMPACT OF SELF-CONFIDENCE ON STUDENTS’ PUBLIC SPEAKING ABILITY - Nurmalasari; M. Tahir; Chairil Anwar Korompot (International Journal of Business English and Communication, 2023)
This study aims: (1) to determine the significant impact of self-confidence on students' public speaking abilities; (2) to find out what causes the lack of confidence in students' public speaking abilities. This study used a quantitative method using simple random sampling technique in taking the sample. The subjects of this study were Business English Communication students’ batch 2020. The types of instruments and data collection techniques were questionnaires with two types, namely open-ended questionnaires and also closed-ended questionnaires. Data analysis used the normality test, simple linear regression test and hypothesis testing. The results showed that there was an impact of self-confidence on students' public speaking abilitiy, meaning that a significance value of 0.005 was less than 0.05 and a value of 2.991 was greater than a of 2.036. So, it can be concluded that there is a significant influence between self-confidence on public speaking or it can be said that is rejected and is accepted, which means that variable X has an effect on variable Y.